Anti-communist films sponsored by the US government in Singapore and Malaya: on the New York Sound Masters Inc. Issue 2 (3rd April 2018) - Hee, Wai-Siam
ABSTRACT: This article examines anti-Communist films made by Hollywood in Cantonese and Malay in Singapore and Malaya in the Cold War context of the "Campaign of Truth." In the early 1950s, the United State Information Agency, an arm of the State Department, secretly commissioned and funded New York Sound Masters Inc. to produce and shoot several anti-Communist films in Singapore and Malaya. In 1953, cinemas across Malaya and Singapore screened Singapore Story and Kampong Sentosa, two Cold War products of the "Campaign of Truth." In addition to analysing the ideology of these films, this article also combines declassified archive material from the US and Singaporean National Archives with primary materials from UK, US, Singaporean, and Malayan periodicals from the Cold War era in order to explore how these two films use Malay and Cantonese to narrate a Hollywood's version of the Singaporean story. As these two films have been largely passed over in scholarship and the films and archives have not been regularly accessible, records of these films are absent from histories of film and television in the US, Singapore, and Malaya. This article aims to remedy this absence.